Cancer incidence among patients attending a tertiary care cancer hospital in central India – A retrospective study - Patel, Lalit Mohan; Kunal Peepre; Haritha VS; Yogesh Tiwari (Asian Journal of Medical Sciences, 2023)
Background: Cancer is a leading cause of mortality and morbidity in the world. Cancer incidence varies widely throughout India from east to west and from north to south making the prevention and control programs difficult the alarming increase of cancer cases in low and middle-income countries like India warrants us to have a better knowledge about the transition in the epidemiology in various parts of the country. Aims and Objectives: The aim of this study was to assess the incidence of different cancers among patients visiting a tertiary care cancer hospital in central India. Materials and Methods: The data were collected retrospectively from the medical record database of a tertiary care cancer hospital in Central India from the time period between January 2017 and December 2021. A total of 13011 patients were registered at our hospital between this time period. Data were analyzed for the site of disease and tabulated, and then, the percentage distribution was calculated. Results: Head-and-neck cancer was the most commonly reported one followed by cervical cancer and breast cancer. Among gynecological malignancies, cervical cancer dominated the spectrum followed by ovarian cancer and endometrial cancer. Tobacco-related cancers were seen in high number each year. Less commonly reported cancers were that of urethral, adrenal, germ cell tumors, and choriocarcinoma followed by that of eye and ear. Conclusion: There is an urgent need to set up stringent hospital-based and population-based cancer registration system to understand the profile of cancer in each geographical region for a better understanding and implementation of cancer control programs.